A New Fragment of Proto-Aeolic Capital from Jerusalem. (June 2015) - Ben-ami, Doron; Tchekhanovets, Yana
Abstract : The article deals with a fragment of a proto-aeolic capital recently found in the Givati Parking Lot excavations in the northwestern sector of the City of David, Jerusalem.